Stability of free and complexed human immunodeficiency virus type 1 antigen at 4 degrees C and at room temperature. - Griffith, B P (1995)
Free and immune-complex-dissociated (ICD) human immunodeficiency virus type 1 (HIV-1) antigenemias in serum specimens stored at room temperature (RT) and 4 degrees C for 1 to 35 days were evaluated. At all time points examined, there was no significant loss in detectable levels of ICD HIV-1 antigen at either RT or 4 degrees C. Free HIV-1 antigen was not stable in serum samples stored at RT for more than 2 days but was stable in samples stored at 4 degrees C for up to 4 days. Loss of free antigen occurred more rapidly in samples with high antigen content at baseline. Use of the ICD antigen assay allowed accurate quantitation of antigen in samples stored at RT or 4 degrees C for as long as 1 month.